RELAÇÃO ENTRE ANSIEDADE SOCIAL E EMPATIA - Oliveira, Maria Silvia Andrietta de (2013)
The social anxiety disorder (SAD) can be described as fear or discomfort in situations where a person believes that their performance is being evaluated by others and when the person fears to behave in a humiliating or embarrassing way. An essential element of this type of symptom is the judgment that these individuals make about the opinions of others. This judgment is closely related to the concept of empathy or the capacity to put yourself in the place of another individual and deduce, even in a distorted way, what this person is thinking or feeling. This project investigated the relationship between empathic capacity and levels of social anxiety in normal subjects. Two questionnaires were applied: Liebowitz Social Anxiety Scale and Interpersonal Reactivity Idex (IRI). Significant correlations were observed among both scales scores, suggesting that the expression of social anxiety demand some empathic capacity. These results justify further investigations on how both phenomena can be associated in terms of neuropsychological mechanisms.